IPTEK BAGI MASYARAKAT (IbM) KELOMPOK TANI PEPAYA DI KECAMATAN LAMURU KABUPATEN BONE - Isnaini, Junyah Leli; Yusuf, Muhammad (Jurnal BALIRESO, 2017)
Techniques cultivation by farmers of papaya crop in the district Lamuru, highly variable, is not optimal and not yet fully apply the recommended technology innovation so that although productivity is not too low, but still need improvement management, especially the system of nutrient / fertilizer to plants. Along the loss of subsidized chemical fertilizer, chemical fertilizer scarcity and high prices in the market become an obstacle in fulfilling the needs of farmers papaya plant nutrients. Therefore, it is necessary to find alternative that function to chemical fertilizers and pesticides is more safe friendly for environmental. TechnologyPosidan-Ht (liquid organic fertilizers, natural pesticides, and growth hormone) is an alternative to chemical fertilizers and pesticides that are safe friendly for environmentally. Objectives and targets outcomes to be achieved from the activities science and technology for the public are: 1) the target output short term that will be produced are: (a) The famers skiled is cultivation of papaya with theuse proper cultivation technology application independently in the crop, (b) famers knows the importance of using posidan -ht, (c) The Famers partners were able to produce their own posidan-ht, (d) ) applying a solution of skilled posidan-ht independently in planting papaya, and 2) Target long-term outcomes that will be produced are: (a) the loss of partners dependence on fertilizer and chemical pesticides in the management of the papaya plant, (b) Provided papaya plants healthy without relying chemical fertilizers and pesticides,(c) Subdistrict Lamuru will Sentra be healthy Organic Papaya that have high bargaining value d) Formed new entrepreneurs who produce posidan- ht. Approach methods are offered to support the realization of the program consists of three methods, namely: 1). Participatory extension, (2) Training (demonstrations and practice activities by participants), (3) Mentoring, coaching the participants by the implementation team, and (4) mentoring methods.